1997
DOI: 10.1038/hdy.1997.189
|View full text |Cite
|
Sign up to set email alerts
|

The maintenance of species differences across a Heliconius hybrid zone

Abstract: A contact zone between Heticonius erato and H. himera in southern Ecuador provides an opportunity to study the transition from races to species in Heliconiine butterflies. Genetic differentiation at 30 allozyme loci (D = 0.28) is five times greater between himera and erato than among races of erato (D <0.062). Analysis of restriction fragment length polymorphisms in an 800-bp region of the mitochondrial genome shows fixed differences between the species.Despite 5-10 per cent hybridization per generation, these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
66
2
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 45 publications
(38 reference statements)
7
66
2
1
Order By: Relevance
“…The M. tredecim/neotredecim contact zone could be similar to that observed by Jiggins et al (1997) for Heliconius erato and H. himera. In these two species, parental genotypes at a number of unlinked gene loci remain in tact despite some hybridization (5-10%) and no apparent hybrid inviability.…”
Section: Should 13-and 17-year Cicadas Be Called Differentsupporting
confidence: 50%
“…The M. tredecim/neotredecim contact zone could be similar to that observed by Jiggins et al (1997) for Heliconius erato and H. himera. In these two species, parental genotypes at a number of unlinked gene loci remain in tact despite some hybridization (5-10%) and no apparent hybrid inviability.…”
Section: Should 13-and 17-year Cicadas Be Called Differentsupporting
confidence: 50%
“…In three cases, H. cydno × H. pachinus , H. erato × H. himera , H. charithonia × H. peruvianus , the hybridizing taxa are parapatric. We consider these to be species pairs operationally on the grounds that intermediates are rare in areas of contact compared with parental forms (Additional File 2) [37,46,51-55]. …”
Section: Resultsmentioning
confidence: 99%
“…Although the initial hybridization can be difficult due to strong assortative mating, genes from hecale , atthis , ismenius , melpomene and cydno in the melpomene-cydno- silvaniform group can apparently be mixed together at will in the laboratory (Additional Files 1, 2; [47]). The similarity of allelic frequencies at some loci, and the strong differences at others in H. himera and H. erato can be explained by selective gene flow at some loci [51]. Two recent studies [54,55] have demonstrated sharing of some, but not all molecular markers between Heliconius melpomene , Heliconius cydno , and H. pachinus .…”
Section: Resultsmentioning
confidence: 99%
“…Reproductive barriers are typically classified based on the stage in the life cycle that they occur (prezygotic or postzygotic) or the factors that act to reduce hybrid fitness (endogenous or exogenous selection) (Jiggins et al 1997;Coyne and Orr 1998;Jiggins and Mallet 2000;Bronson et al 2003;Hurt et al 2005). Some have suggested strong mate selection (Mendelson 2003) or body size differences (McKinnon et al 2004) will facilitate development of prezygotic barriers.…”
Section: Introductionmentioning
confidence: 98%